Nature-based solutions for urban climate change adaptation: linking the science, policy, and practice community for evidence-based decision-making - Collier, Marcus (My University, 2019)
Nature-based solutions offer an exciting prospect for resilience building and advancing urban planning to address complex urban challenges simultaneously. In this article, we formulated through a coproduction process in workshops held during the first IPCC Cities and Climate Science Conference in Edmonton, Canada, in March 2018, a series of synthesis statements on the role, potential, and research gaps of nature-based solutions for climate adaptation and mitigation. We address interlocking questions about the evidence and knowledge needed for integrating nature-based solutions into urban agendas. We elaborate on the ways to advance the planning and knowledge agenda for nature-based solutions by focusing on knowledge coproduction, indicators and big data, and novel financing models. With this article, we intend to open a wider discussion on how cities can effectively mainstream nature-based solutions to mitigate and adapt to the negative effects of climate change and the future role of urban science in coproducing nature-based solutions.
Keywords: Nature-based solutions; Cities; Climate change; Resilience; Urban; Smart & Sustainable Planet; COMMUNITY; Community of Practice; Environmental Policy; NATURE-BASED SOLUTIONS; Science Planning/Policy; Science and environmental policy; climate policy; Community; Environment and housing; Policy